Potencial da nisina no controle de Staphylococcus aureus resistente (MRSA) e sensível (MSSA) à meticilina - Silva, César Matos Ribeiro da (2018)
Staphylococcus aureus has been considered a major public health problem worldwide due mainly to the ability to develop resistance to antibiotics. The prevalence of methicillin resistant strains of S. aureus (MRSA) in both hospital and community settings has been increasing, with cases of infections and deaths reported in healthy children and adults. Bacteriocins have been identified as promising alternatives for the control of this pathogen. However, besides the therapeutic use of these peptides still not approved, some studies indicate the possibility of selection of resistant strains. Therefore, prior to the therapeutic use of bacteriocins, studies must be carried out to understand the effect that bacteriocin may have on the selection of resistant strains to avoid the current problem with lineages resistant to traditional antibiotics. In view of the above, the objective of this study was to verify the antimicrobial activity of nisin against strains of MRSA and MSSA isolated from the oropharynx of health professionals and verify the selection of strains resistant to bacteriocin. For the genotypic characterization of the MRSA and MSSA strains, the nucA, LuckPV, mecA and mecC genes were tested. The MSSA lines were positive for amplification of the nucA gene only, confirming the identification of genus and species of these strains. For MRSA strains, the only gene that was not detected was mecC, confirming the methicillin resistance phenotype and that these strains are of human origin and of community environments. The results obtained by the agar diffusion test demonstrated that 80% of the MSSA strains (n = 30) were inhibited by nisin and only one MRSA line (n = 6) showed no sensitivity to bacteriocin. The MIC of MSSA strains ranged from 97.7 to 1250 IU / mL and from MRSA strains of 937.50 to 5000 IU / mL. The DBM for MSSA strains varied from 97.7 IU / mL to values greater than 50,000 IU / mL, and for MRSA, this variation was between 5000 IU / mL at values greater than 10,000 IU / mL depending on the lineage. For most lineages DBM was higher than MIC, showing that the effect of bacteriocin depends on bacteriocin concentration: low concentrations exert bacteriostatic effect and high concentrations bactericidal effect. The addition of increasing concentrations of the bacteriocin to the BHI medium generally resulted in the increase in the lag phase and decrease in the specific growth rate and maximal DO reached by the MSSA and MRSA cultures. MSSA and MRSA strains were transferred for approximately 30 generations in the presence of bacteriocin and a decrease in sensitivity was observed with a consequent increase in nisin MIC for all strains tested. The bacteriocin resistance phenotype has been shown to be a stable trait for these strains and may be associated with a genetic factor. It has also been observed that the use of nisin may trigger cross-resistance to some antibiotics. The results obtained demonstrated that nisin is efficient in controlling the growth of MSSA and MRSA. However, the fact that these lines demonstrate resistance to bacteriocin after transfer in the presence of the same indicates the need to develop strategies to avoid in the future the current problem of resistance to antibiotics. The best way to use bacteriocins therapeutically is to suggest that it is in combination with traditional antibiotics.